Synergy of Sports and Leadership: Community Soccer Impact on SDGs Achievement in Leo-Leo Village, Morotai Island - Pratiwi, Febriana; Papingka, Gullyt Karlos Papingka; Syahid Nuryasin (Universitas Majalengka, 2025)
Background: This research explores the phenomenon of community soccer in Leo-Leo Village, Pulau Rao District, Morotai Island Regency, and its impact on shaping young leaders who contribute to the achievement of the Sustainable Development Goals (SDGs). Purpose: The research focuses on two main questions: (1) how community soccer can serve as a means to shape young leaders, and (2) how soccer can be integrated with the Sustainable Development Goals (SDGs). This research is expected to provide in-depth insights into the experiences of individuals involved in community soccer in Leo-Leo Village, as well as its impact on leadership development and education. Methods: Using a phenomenological approach, this study gathers the experiences and perspectives of players, coaches, and community members to understand how participation in community soccer can develop leadership skills and social values relevant to sustainable development goals. Results: The results of the study indicate that community soccer serves as an essential platform for youth to learn about cooperation, discipline, and responsibility. Additionally, participation in these activities raises their awareness of social and environmental issues aligned with the SDGs, such as quality education and reducing inequalities. However, there are challenges such as limited facilities and lack of external support that hinder the development of this program. Conclusion: These findings are expected to provide insights for stakeholders in creating an environment that supports youth leadership development through community soccer in the context of the SDGs. Implications and Recommendation: This research recommends expanding collaboration between the government, non-governmental organizations, and the community to maximize the potential of soccer as a means of forming future leaders.